Evaluasi Kebijakan Program Pendidikan Inklusif Di SDN Betet 1 Kota Kediri - Yusuf Juniar Dewantara; Frida Kusumastuti (Jurnal Kebijakan dan Pengembangan Pendidikan, 2020)
Abstract: This study aims to evaluate the implementation of inclusive education programs. The method used is a qualitative analysis that is describing and interpreting data from each component evaluated using the CIPP evaluation model (Context, Input, Process, Product). Data sources in this study include the principal, principal teacher, special assistant teacher (GPK), school committee, parents of students and special needs students. Data collection is done by interview, observation, a document study, and documentation. The findings in the context component show that the legal basis for implementing inclusive education is by the prevailing Education System Law in Indonesia. The objectives of inclusive education are by the established formula. The findings of the input component show that there are quite a several ABK inputs in school with a variety of types of disability by the Inclusive Education Law. However, the SDM component especially GPK and infrastructure still need attention to improve and complete it. The findings of the process component show that the process of student acceptance, teaching and learning activities and student assessment have adjusted to the applicable regulations. But there are still students who are not supposed to go to an inclusive school to study at the school. The findings of the product component indicate that there are achievements achieved by inclusive students and the positive impact of implementing inclusive education. This research provides recommendations for the government and schools implementing inclusive education to continue implementing the program and continue to communicate and collaborate with institutions and several related parties in carrying out inclusive education programs to be more optimal.Key Words: Program Evaluation, Inclusive Education, CIPP Model Abstrak: Penelitian ini bertujuan untuk mengevaluasi implementasi program pendidikan inklusif. Metode yang digunakan adalah analisis kualitatif yaitu mendeskripsikan dan memaknai data dari masing-masing komponen yang dievaluasi dengan menggunakan model evaluasi CIPP (Context, Input, Process, Product). Sumber data dalam penelitian ini meliputi kepala sekolah, guru utama, guru pendamping khusus (GPK), komite sekolah, orang tua/wali murid dan siswa ABK. Pengumpulan data dilakukan dengan wawancara, observasi, studi dokumen dan dokumentasi. Hasil temuan pada komponen konteks menunjukkan bahwa landasan hukum penyelenggaraan pendidikan inklusif sudah sesuai dengan Undang-Undang Sistem Pendidikan yang berlaku di Indonesia. Tujuan pendidikan inklusif sudah sesuai dengan rumusan yang telah ditetapkan. Hasil temuan komponen input menunjukkan input ABK yang bersekolah jumlahnya cukup banyak dengan berbagai jenis ketunaannya sesuai yang tercantum pada Undang-Undang Pendidikan Inklusif. Namun pada komponen SDM terutama GPK dan sarana prasarana masih memerlukan perhatian untuk meningkatkan dan melengkapinya. Hasil temuan komponen proses menunjukkan proses penerimaan siswa, kegiatan belajar mengajar dan penilaian siswa telah menyesuaikan dengan peraturan-peraturan yang berlaku. Namun masih ada siswa yang tidak seharusnya masuk di sekolah inklusif menempuh pendidikan di sekolah tersebut. Hasil temuan komponen produk menunjukkan terdapat prestasi yang berhasil diraih oleh siswa inklusif dan dampak positif dari pelaksanaan pendidikan inklusif. Penelitian ini memberikan rekomendasi untuk pemerintah dan pihak sekolah penyelenggara pendidikan inklusif agar tetap melaksanakan program tersebut dan terus berkomunikasi serta berkolaborasi dengan lembaga dan beberapa pihak terkait dalam menjalankan program pendidikan inklusif agar lebih optimal.Kata Kunci: Evaluasi Program, Pendidikan Inklusif, Model CIPP